2017
DOI: 10.1080/01658107.2017.1318406
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Optic Disc Oedema by Bortezomib and Dexamethasone Followed by Autologous Peripheral Blood Stem Cell Transplantation in Patient with POEMS Syndrome

Abstract: The authors present findings in a 39-year-old man with polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome with bilateral optic disc oedema. He was successfully treated with bortezomib and dexamethasone followed by autologous peripheral blood stem cell transplantation. The peripapillary retinal thickness was reduced in the optical coherence tomographic (OCT) images along with a decrease of the serum vascular endothelial growth factor (VEGF) levels. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies have shown that choroidal vessels, in comparison to retinal vessels, may be more susceptible to serum VEGF level due to its larger caliber and flow volume. Circulating VEGF in choroidal vessels is more likely to leak out, binding to abluminal VEGFR2 to improve permeability of surrounding vessels [6,20,21]. Besides, there is an area with a defective blood-retinal barrier surrounding the optic disc, called the tissue of Elschnig border, where substances in choroidal vessels could leak out even more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that choroidal vessels, in comparison to retinal vessels, may be more susceptible to serum VEGF level due to its larger caliber and flow volume. Circulating VEGF in choroidal vessels is more likely to leak out, binding to abluminal VEGFR2 to improve permeability of surrounding vessels [6,20,21]. Besides, there is an area with a defective blood-retinal barrier surrounding the optic disc, called the tissue of Elschnig border, where substances in choroidal vessels could leak out even more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating VEGF in choroidal vessels is more likely to leak out , binding to abluminal VEGFR2 to improve permeability of surrounding vessels. [6,21,22] Besides, there is an area with a defective blood-retinal barrier surrounding the optic disc, called the tissue of Elschnig border, where substances in choroidal vessels could leak out even more easily. Thus, ODE in POEMS syndrome is probably the result of choroidal edema caused by high serum VEGF level.…”
Section: Ode Area and Peripapillary Retinal Thickness (Prt)mentioning
confidence: 99%
“…[20] Due to the caliber and flow volume differences between choroidal and retinal vessels, circulating VEGFA can only leak out from choroidal vessels and bind to abluminal VEGFR2 to improve permeability of surrounding vessels. [6,[20][21][22] Also, previous study reported that subfoveal choroidal thickness was positively related to serum VEGF level in POEMS syndrome. [4] These findings together suggested that circulating VEGF triggered ODE in patients with POEMS syndrome through choroid, which could only be relieved through systemic treatment.…”
Section: Ode Area and Peripheral Retinal Thicknessmentioning
confidence: 99%